Comparative Effect of rhPTH(1‐84) on Bone Mineral Density and Trabecular Bone Score in Hypoparathyroidism and Postmenopausal Osteoporosis. (8th August 2018) - Cipriani, Cristiana; Pepe, Jessica; Silva, Barbara C; Rubin, Mishaela R; Cusano, Natalie E; McMahon, Donald J; Nieddu, Luciano; Angelozzi, Maurizio; Biamonte, Federica; Diacinti, Daniele; Hans, Didier; Minisola, Salvatore; et al.
ABSTRACT: Parathyroid hormone (PTH) (1‐84) improves lumbar spine (LS) areal bone mineral density (aBMD) and trabecular bone score (TBS) in hypoparathyroidism over a 2‐year treatment period. Studies in osteoporosis have shown that with PTH(1‐34) there is a significant increase in LS aBMD and TBS. In this article, we provide new data comparing the effects of the same form of PTH, namely recombinant human PTH, rhPTH(1‐84), on aBMD and TBS in hypoparathyroid and osteoporotic patients over an 18‐month treatment period. We studied 19 premenopausal (mean age 45.8 ± 11.8 years) and 16 postmenopausal (71 ± 8.4 years) hypoparathyroid women and 38 women with postmenopausal osteoporosis (71 ± 8.3 years). DXA (hologic) at LS, femoral neck, total hip, and distal one‐third radius was assessed. Site‐matched LS TBS data were extracted from deidentified spine DXA scans using the TBS iNsight software (version 2.1; Medimaps, Geneva, Switzerland). We observed a significant increase in LS aBMD in premenopausal and postmenopausal hypoparathyroid (3 ± 1.1%, p  < 0.02 and 3.1 ± 1.4%, p  < 0.05, respectively) and osteoporosis (6.2 ± 1.1%, p  < 0.0001) patients after 18 months. There was a significant increase (3 ± 1.5%, p  = 0.05) in TBS in premenopausal hypoparathyroid patients. A change in TBS was not observed in either postmenopausal group. One‐third radius aBMD significantly declined in postmenopausal hypoparathyroid (‐3.6 ± 1.1%, p  < 0.01) and osteoporosis (‐8 ± 1.4%, p  < 0.0001) patients. Overall, there was a significantly greater increase in TBS in premenopausal hypoparathyroid than in osteoporosis patients ( p  < 0.0001) after adjusting for baseline values, age, BMI, and average daily dose of rhPTH(1‐84). Comparing only postmenopausal women, the LS aBMD increase was greater in osteoporotic than hypoparathyroid subjects ( p  < 0.01). Our results demonstrate that rhPTH(1‐84) administered for 18 months increases trabecular aBMD in hypoparathyroidism and postmenopausal osteoporosis with greater gains observed in the subjects with osteoporosis. The data suggest different effects of PTH on bone depending on the baseline skeletal structure, skeletal dynamics, compartments, and menopausal status. © 2018 American Society for Bone and Mineral Research.